Communication patterns and adaptation in maintaining academic culture among women leaders: a study of symbols and rituals at the University of Lampung (2023–2024) - Trenggono, Nanang; Wardhani, Andy Corry; Ashaf, Abdul Firman; Aryanti, Nina Yudha; Kartika, Tina (Frontiers in Communication, 2025)
The communication pattern of the University of Lampung’s rector for 2023–2024 is noteworthy, portraying a distinct knowledge framework. Two critical issues arise, namely, (1) the recurrent decline in institutional performance during leadership transitions at Unila, and (2) corruption scandals encompassing university leaders in 2022. To address these issues, the current work adopted a cultural communication perspective. Peters suggested that communication can be identified through various messages, events, and behaviors. Data were collected using a constructive research method, primarily through intensive interviews. Study identified three key communication patterns. First, the rector introduced the slogan “Be Strong,” initially launched without adequate socialization, symbolizing resilience and institutional recovery amidst challenges. Second, drawing from Carey’s ritual communication perspective, the focus was on internal dynamics to foster a strong academic community. Third, while leadership communication lacks a robust application of symbols and rituals, it demonstrates efforts to preserve academic culture. These patterns highlight the leader’s adaptive strategies in navigating challenges and fostering acceptance and trust within the academic community.